2008
DOI: 10.2320/jinstmet.72.538
|View full text |Cite
|
Sign up to set email alerts
|

Friction Stir Weldability of High Tensile Strength Mg-Zn-Al-Ca-La Magnesium Alloy Consisted of Fine Grain

Abstract: Table 1 Chemical composition of magnesium alloy used (mass).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…7) By using RCP, high strength Mg alloys with fine-grained structures have been produced, and their weldability has been investigated. 8,9) In order to broaden the application of Mg alloys in transportation industries, the joining of Mg alloys to aluminum (Al) alloys becomes important and necessary. In the dissimilar joint of Mg and Al alloys, intermetallic compound (IMC) is always generated.…”
Section: Introductionmentioning
confidence: 99%
“…7) By using RCP, high strength Mg alloys with fine-grained structures have been produced, and their weldability has been investigated. 8,9) In order to broaden the application of Mg alloys in transportation industries, the joining of Mg alloys to aluminum (Al) alloys becomes important and necessary. In the dissimilar joint of Mg and Al alloys, intermetallic compound (IMC) is always generated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, FSW of high melting temperature materials such as steels, nickel and Ti alloys has become a research hotspot [16][17][18]. Though FSW of conventional magnesium alloys has been intensively investigated, especially for the MgAl-Zn (AZ) series [19][20][21][22][23], few studies dedicated to non-combustive magnesium alloys have been reported [24][25][26][27]. Zhang et al [24] studied microstructural evolution of the non-combustive Mg-6%Al-3%Ca-0.5%R.E.-0.2%Mn magnesium alloy due to friction stir welding.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [24] studied microstructural evolution of the non-combustive Mg-6%Al-3%Ca-0.5%R.E.-0.2%Mn magnesium alloy due to friction stir welding. Yamamoto et al [25] and Chen et al [26] conducted friction stir spot welding and friction stir welding of non-combustive Mg-6%Al-0.5%Mn-2% Ca (AMX602) magnesium alloy, respectively. Choi et al [27] made microstructure evaluation of friction stir welded AZ91 with CaO non-combustive Mg Alloy.…”
Section: Introductionmentioning
confidence: 99%
“…,AZ61 合金 3,4) ,AZ91 合金 5,6) ,難燃性 Mg 合金 7) , 耐熱 Mg 合金継手 8) および微細結晶粒を有する高強度 Mg 合 金 9,10) に関するものがあり,継手強度は母材引張強度の約 80…”
unclassified